PEMATAHAN DORMANSI BENIH KELAPA SAWIT (Elaeisguineensis Jacq.) DENGAN BERBAGAI KONSENTRASI KALIUM NITRAT (KNO3) DAN PENGARUHNYA TERHADAP PERTUMBUHAN BIBIT PADA TAHAP PRE NURSERY - Saputra, Deni; Zuhry, Elza; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This subject proposes to find out the result of oil palm seed immersion in various concentrations of KNO3 and to get the best KNO3 concentration on germination and outgrowth. This research has been conducted at Plant Breeding and Experimental Plantation Laboratory, Faculty of Agriculture, University of Riau. The study was conducted for 4 months from Agust to December 2016. The experiment was conducted experimentally using Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. The treatment of soaking of scarificated oil palm seed in KNO3 (K) concentration for 20 hours consisted of K0 (soaking without KNO3), K1 (0.2%), K2 (0.4%), K3 (0.6%). Parameters observed were ; germination time, index value test, percentage of sprouts, radicle length, plumule length, seed height, and seedling dry weight. The data obtained were analyzed statistically by using analysis of variance and means separation with Duncan Multiple Range Test at 5%. The result showed that soaking of oil palm seed in KNO3 solution had a significant effect on sprouts, germination percentage, radicle length, plumule length and dry weight of seedlings. Soaking of oil palm seed in a KNO3 solution with a concentration of 0.4% for 20 hours can accelerate when sprouts appearing from 22.4 days to 6.8 days, and increase germination rates from 34.4% to 53.6%. Key Words : Oil palm seed, dormancy, KNO3 and germination